Bodily injury by fault in the New Romanian Criminal Code - Zazula Bela Attila (Journal of Legal Studies, 2016)
In all constitutional systems, there is a reticence in sanctioning criminally any injury caused by fault to a person, without taking into account certain aspects really justifying the penology’s intervention – a severe injury of the victim’s body, a case where there are broken prudence norms enacted precisely for avoiding the bodily injury by fault of a person.